VD_FINDINFO HC / 2021 / 126 vom 2. März 2021 - VD Tribunal cantonal (2021)
RÉSILIATION, COMPÉTENCE RATIONE MATERIAE, DROIT D'ÊTRE ENTENDU, DÉLAI, NOTIFICATION ÉCRITE | 132 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 59 al. 2 let. b CPC (CH)